Teachers' styles of resolving interpersonal conflicts with students in elementary schools - Bulić Aid (Specijalna Edukacija i Rehabilitacija, 2018)
Teachers' styles of resolving conflicts with students are at the same time behavioral examples which students observe and might adopt. Depending on the nature of the conflict resolution i.e. if it is constructive or destructive in nature, they can represent protective factors or factors of risk in students' development. With regard to that, the aim of our research was to determine conflict resolution styles that teachers use at schools and examine possible differences in those styles in regard to teachers' gender, age and length of service. The sample consisted of 116 teachers from seven elementary schools based in the city of Tuzla. The instruments used in this research were: a questionnaire with questions about gender, age and length of service, and a modified scale for measuring conflict resolution styles ROCHI-II (Rahim, 1983). The findings of this research show that constructive conflict resolution styles are used more often than destructive ones. No significant differences in styles were observed with regard to gender or age, but there were significant differences with regard to the length of service. More experienced teachers used adaptive style more often when resolving conflicts with students. The findings have shown that the democratization processes and constructive communication between teachers and students are more frequent and represent a protective factor against disorders in students' behavior. However, rare occurrences of destructive conflict resolution styles, as risk factors for disorders in students' behavior, are a sign that further education in the field of educational communication is needed, while taking into account differences between teachers' styles depending on the length of service.